Entrevista periodística en los programas radiales de Babahoyo - Moyano Guevara, Andrea Estefanía (2021)
Radio is currently one of the most popular, accessible and mass media of social communication, as well as the one that has a relevant influence on public opinion and is in force in all social strata. It is accentuated by its undivided particularities: timeliness, immediacy, speed, haste and the ability to be understood by a very large and diverse audience. This means of broadcasting allows a refreshing way of sharing information, since it allows externalizing varied voices, which forges that the news progress is active and fast for the radio listener. This application of preparations and practices generates a strong impact where the listener stays tuned in and interacts with the radio programming and obtains a valuable range of credibility. By referring to an interview in a news or variety program, this generates that this becomes more attractive to the user who tunes in daily to the radio. The main objective of the interview is to documentally investigate a third party, whether a social or political figure, through a sequence of questions that allow to be prepared at the time of interviewing and reflect security when conducting them. When conducting an interview in a radio news program, time is limited, so the interview must be precise, without digressions, understandable, in order to obtain the information required. The radio provides the opportunity to get a wide audience with a minimum budget, compared to other media.